"Opt out" or kept out? The effect of stigma, structure, selection, and sector on the labor force participation of married women in India. Issue 3 (19th May 2020) - Datta Gupta, Nabanita; Nandy, Debasish; Siddhanta, Suddhasil
Abstract: Using the 61st and 68th rounds of National Sample Survey data, we investigate the role of stigma, the economy's structure, potential selection bias, and sectoral differences in explaining the low labor force participation (LFP) of middle and secondary educated women in India relative to low‐ and high‐educated women (the "U‐shape"). Estimating LFP regressions on a sample of prime‐aged married women, we show that, controlling for background characteristics, if a woman's husband works in a white‐collar job in a region with a high share of blue‐collar jobs, she is less likely to participate in the labor market (stigma). We also find a positive effect of an increase in an index of white‐collar job growth (structure) on married women's LFP. These effects are present in both rural and urban sectors but are strongest in the rural sector. However, middle and secondary educated women are still found to have substantially lower LFP than low‐ and graduate‐educated women in both sectors. Indeed, over time, the U‐shape persists in the rural sector and deepens in the urban sector. Because unobservables are quite large in the urban sector, we use the method of instrumental variables and find an increasing return at middle levels but stagnation at higher levels.